2009
DOI: 10.1242/jcs.048579
|View full text |Cite
|
Sign up to set email alerts
|

Cayman ataxia protein caytaxin is transported by kinesin along neurites through binding to kinesin light chains

Abstract: Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 31 publications
(51 reference statements)
2
49
1
Order By: Relevance
“…3B). This LEWD motif is similar to binding motifs described in other KLC-binding proteins (Aoyama et al, 2009;Dodding et al, 2011;Konecna et al, 2006;Schmidt et al, 2009). Analysis of the KLC-binding region of nesprin-4 also revealed the presence of the LEWD motif, though the flanking sequences were less conserved (Fig.…”
Section: Recruitment Of Exogenous Kif5b To the Nuclear Envelope Rescusupporting
confidence: 76%
“…3B). This LEWD motif is similar to binding motifs described in other KLC-binding proteins (Aoyama et al, 2009;Dodding et al, 2011;Konecna et al, 2006;Schmidt et al, 2009). Analysis of the KLC-binding region of nesprin-4 also revealed the presence of the LEWD motif, though the flanking sequences were less conserved (Fig.…”
Section: Recruitment Of Exogenous Kif5b To the Nuclear Envelope Rescusupporting
confidence: 76%
“…Functional studies of Drosophila Klc suggest that it is not important for normal mitochondrial distribution in photoreceptor axons (Glater et al, 2006) and that it is dispensable in the binding of kinesin to mitochondrial adaptor proteins (MacAskill et al, 2009;Wang and Schwarz, 2009). However, recent work on caytaxin, a protein implicated in human ataxia, has shown that it binds to Klc, associates with mitochondria and influences mitochondria distribution in cultured cell neurites (Aoyama et al, 2009). Although caytaxin might be unique to vertebrates, further investigation of the possibility that in some cells Klc can influence mitochondria as well as vesicle transport seems warranted.…”
Section: Regulation Of Axonal Mitochondria Transportmentioning
confidence: 99%
“…Many studies reported that caytaxin plays an important role in axonal transporting [65], glutamate synthesis [66], synaptic apoptosis, and neurodegenerative diseases [67]. By using coimmunoprecipitation and mass spectrum detection, our unpublished preliminary results showed that DAPK1 could also interact and phosphorylate caytaxin on serine 46 at the presynaptic area in the mice model of middle cerebral artery occlusion (MCAO).…”
Section: Dapk1 and Caytaxinmentioning
confidence: 85%